2019
DOI: 10.1016/j.camwa.2019.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Superconvergence of numerical gradient for weak Galerkin finite element methods on nonuniform Cartesian partitions in three dimensions

Abstract: A superconvergence error estimate for the gradient approximation of the second order elliptic problem in three dimensions is analyzed by using weak Galerkin finite element scheme on the uniform and non-uniform cubic partitions. Due to the loss of the symmetric property from two dimensions to three dimensions, this superconvergence result in three dimensions is not a trivial extension of the recent superconvergence result in two dimensions [22] from rectangular partitions to cubic partitions. The error estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…Observe that a superconvergence theory in the H 1 ‐norm has been developed in for the diffusion equation on rectangular partitions; a slight modification of the analysis there will yield a superconvergence of order Oh2 for the SWG solutions of the full convection–diffusion equation (1.1) and (1.2).…”
Section: Swg On Polymeshmentioning
confidence: 99%
See 2 more Smart Citations
“…Observe that a superconvergence theory in the H 1 ‐norm has been developed in for the diffusion equation on rectangular partitions; a slight modification of the analysis there will yield a superconvergence of order Oh2 for the SWG solutions of the full convection–diffusion equation (1.1) and (1.2).…”
Section: Swg On Polymeshmentioning
confidence: 99%
“…From (2.3), the linear extension of u b ∈ W ( T ) can be represented as (see Lem. 6.1 in for details) sub=γ0+γ1xxT+γ2yyT, where leftγ0=|e1|ub,1+ub,2+|e3|ub,3+ub,42|e1|+2|e3|,γ1=ub,2ub,1/|e3|,γ2=ub,4ub,3/|e1|. It follows that ()ubfrakturs()ub()M1=()ubfrakturs()ub()M2=e32()||e1+||e3()ub,1+ub,2ub,3ub,4, …”
Section: Discrete Maximum Principlementioning
confidence: 99%
See 1 more Smart Citation
“…The usual regularity of the approximating functions is compensated by carefully-designed stabilizers. This WG method has been investigated for solving numerous model PDEs; see a limited list of references and references therein [12,18,19,23,37,34,31,32,33,13,14,35,36]. The research results indicate that the WG method has shown its great potential as a powerful numerical tool/technique in scientific computing.…”
mentioning
confidence: 99%
“…So far all weak Galerkin finite element methods with stabilizers do not have superconvergence in both an energy norm and the L 2 norm. A order one superconvergence in an energy norm only is derived in [4,3]. The new method reduces the computation cost greatly of the other WG methods.…”
mentioning
confidence: 99%